(untitled) (TSUL LEGAL REPORT, 2026)
The author separately analyzed the classification of tax audits and types of tax audits. The purpose of this study is to develop, as a result of the study, proposals and conclusions aimed at clarifying the types of tax audits characteristic of the legal nature of the research being carried out. A tax audit is the main legal instrument of tax authorities and must have specific forms and types as an effective means of influencing taxpayers. Otherwise, the number of cases of illegal audits by tax authorities and violations of the rights and interests of taxpayers will increase. Therefore, it is important to clearly define in the Tax Code the legal basis for the classification of tax audits and the scope of powers of each type. Types of tax audits are based on the effectiveness of methods and means of illuminating the object of taxation, and ensuring discipline of state budget revenues without causing harm to taxpayers is the main issue. These issues are studied through a comparative analysis of the legislation of domestic and foreign countries, using historical, legal, systemic, logical, statistical, and other methods. National legislation has developed proposals for the classification, types, and scope of activities that can be carried out during a tax audit. These proposals are used in scientific activity, lawmaking, law enforcement, interpretation of tax legislation, and improvement of national legislation. There are two types of tax audits of a legal nature: desk and on-site audit methods.